2022
DOI: 10.1177/08927057211067702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the silane coupling agent on the physicomechanical properties of EPDM/SBR/AL2O3 rubber blend nanocomposites

Abstract: In this study, ethylene propylene diene rubber (EPDM)/styrene–butadiene rubber (SBR) blend nanocomposites filled with alumina (Al2O3) nanoparticles were prepared. Al2O3 nanoparticles were used with or without surface treatment by the silane coupling agent bis[3 (triethoxysilyl)propyl]tetrasulfide, and Al2O3 nanoparticle–filled EPDM/SBR was compared with carbon black. The influences of the filler type, size, concentration, and surface property on the curing characteristics, degree of filler dispersion, mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…There is also a tetrasulfide group in the molecule of TESPT, which participates in rubber curing. This forms chemical bonding between nanoparticles and rubber chains, improving nanocomposite properties. ,, …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also a tetrasulfide group in the molecule of TESPT, which participates in rubber curing. This forms chemical bonding between nanoparticles and rubber chains, improving nanocomposite properties. ,, …”
Section: Introductionmentioning
confidence: 99%
“…This forms chemical bonding between nanoparticles and rubber chains, improving nanocomposite properties. 2,7,12 Ansarifar et al 5 studied the effects of using TESPT-grafted silica nanoparticles on the mechanical properties of styrene butadiene (SBR), butyl (BR), NBR, and natural (NR) rubbers. It was found that using the modified nanoparticles caused a lowered need for the incorporation of a vulcanization agent (i.e., sulfur).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blends of EPDM/styrene butadiene rubber (SBR) have been analyzed by some authors [ 73 , 74 , 75 ] regarding the effect of different nanocomposite blends, such as reinforcing agents, and the consequent impact on mechanical properties. Broad engineering applications can be found using these kinds of (EPDM/SBR) rubber compounds, such as tires, seals, conveyor belts, and electrical cables, among others.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer blend is a well-known approach in the rubber industry to create rubber compounds with specific properties that cannot be attained from individual polymers. Polymer blends' objectives include improving the physicomechanical, swelling properties, cost-effective material, high aging characteristics and long service life (Khimi and Pickering, 2014;Jong, 2018;Abdelsalam et al, 2022). Most polymer blends are immiscible due to the lack of interactions between the components of blends at the interfaces, whereas a compatibilizer should be incorporated between the components of blends (Jong, 2018;Abdelsalam et al, 2019Abdelsalam et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%